Tools for detecting entanglement between different degrees of freedom in quadrature squeezed cylindrically polarized modes - Gabriel, C.; Aiello, Andrea; Berg-Johansen, S.; Marquardt, Christoph; Leuchs, Gerd (European Physical Journal D, 2012)
Quadrature squeezed cylindrically polarized modes contain entanglement not only in the polarization and spatial electric field variables but also between these two degrees of freedom [C. Gabriel et al., Phys. Rev. Lett. 106, 060502 (2011)]. In this paper we present tools to generate and detect this entanglement. Experimentally we demonstrate the generation of quadrature squeezing in cylindrically polarized modes by mode transforming a squeezed Gaussian mode. Specifically, -1.2dB ± 0.1 dB of amplitude squeezing are achieved in the radially and azimuthally polarized mode. Furthermore, theoretically it is shown how the entanglement contained within these modes can be measured and how strong the quantum correlations are, depending on the measurement scheme. © EDP Sciences, Società Italiana di Fisica, Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-06-05